Bankruptcy proceedings for sovereign state insolvency and their effect on capital flows - Jonathan P. Thomas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
The paper examines the main issues involved in translating domestic bankruptcy procedures to the sovereign context. It considers some of the principles by which domestic bankruptcy procedures operate, and the extent to which they apply to international lending. Two recent proposals are considered in more detail, that of Krueger (`A New Approach to Sovereign Debt Restructuring') and that of Pettifor (`Resolving International Debt Crises – The Jubilee Framework for International Insolvency'). The paper also considers the question of the ex ante effects of a procedure which makes default less costly, and concludes that despite a negative impact on the ability to borrow, the overall welfare effect need not be negative.
Keywords: F34; 330; sovereign debt; bankruptcy; capital flows; Chapter 11; Staatsbankrott; Auslandsverschuldung; Auslandsschuldendienst